2014
DOI: 10.1155/2014/380316
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Assimilation byLactobacillusProbiotic Bacteria: AnIn VitroInvestigation

Abstract: Excess cholesterol is associated with cardiovascular diseases (CVD), an important cause of mortality worldwide. Current CVD therapeutic measures, lifestyle and dietary interventions, and pharmaceutical agents for regulating cholesterol levels are inadequate. Probiotic bacteria have demonstrated potential to lower cholesterol levels by different mechanisms, including bile salt hydrolase activity, production of compounds that inhibit enzymes such as 3-hydroxy-3-methylglutaryl coenzyme A, and cholesterol assimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 31 publications
10
72
0
5
Order By: Relevance
“…The kefir isolates reduced the level of cholesterol up to 51.6% for 24 h in the modified MRS medium. A previous study showed that some Lactobacillus reuteri strains reduced the level of cholesterol from 20.18 to 59.94%, and some Lactobacillus acidophilus strains reduced the level from 49.57 to 55.43% for 24 h ; these results are consistent with the results of the present study. In contrast, another study reported that Lactobacillus casei and Lactobacillus sakei reduced the level of cholesterol by approximately 30% and Pediococcus acidilactici did so by 20% for 24 h .…”
Section: Discussionsupporting
confidence: 93%
“…The kefir isolates reduced the level of cholesterol up to 51.6% for 24 h in the modified MRS medium. A previous study showed that some Lactobacillus reuteri strains reduced the level of cholesterol from 20.18 to 59.94%, and some Lactobacillus acidophilus strains reduced the level from 49.57 to 55.43% for 24 h ; these results are consistent with the results of the present study. In contrast, another study reported that Lactobacillus casei and Lactobacillus sakei reduced the level of cholesterol by approximately 30% and Pediococcus acidilactici did so by 20% for 24 h .…”
Section: Discussionsupporting
confidence: 93%
“…Percentage of cholesterol assimilation by L. plantarum IIA-1A5 was higher than that of L. fermentum B111K, while in assimilated cholesterol of 10 10 cells, the value of L. fermentum B111K was higher than L. plantarum IIA-1A5. The similar result was reported by Tomaro-Duchesneau et al (2014) that percentage of cholesterol assimilation of Lactobacillus reuteri NCIMB 702656 was higher compared to L. plantarum ATCC 14917, while in assimilated cholesterol of 1010 cells, L. plantarum ATCC 14917 showed the higher value than L. reuteri NCIMB 702656.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in the assimilation ability were confirmed by previous study of Tomaro-Duchesneau et al (2014) …”
Section: Cholesterol Assimilationsupporting
confidence: 79%
See 1 more Smart Citation
“…Table 4 Clinical studies of lactobacilli showing efficacy for treatment of hypercholesterolaemia Cholesterol assimilation has also been evaluated as a possible therapeutic approach to reduce the risk for cardiovascular diseases. 114 In this regard, Tomaro-Duchesneau and coworkers investigated the ability of 11 L. strains (L. reuteri NCIMB 11951, 701359, 702655, 701089 and 702656, L. fermentum NCIMB 5221, 8829, 2797, L. rhamnosus ATCC 53103 GG, L. acidophilus ATCC 314 and L. plantarum ATCC 14917) to assimilate cholesterol. While L. plantarum ATCC 14917 was the best cholesterol assimilator in de Man, Rogosa and Sharpe broth, L. reuteri NCIMB 701089 assimilated over 67% of cholesterol under physiological intestinal conditions.…”
Section: Cholesterol-lowering Activitymentioning
confidence: 99%